Validity and Reliability of Persian Version of Coping Style (Approach and Avoidance) Inventory in Iranian Athletes - Mohsen Purmenati; Hassan Gharayagh Zandi; Elahe Arab Ameri (University of Tehran, 2015)
Stress is a natural phenomenon in sport competitions. An athlete may maintain good performance and achieve success when he can deal with stress. The present study aimed at examining the validity and reliability of Anshel and Kaissidis's Coping Style Inventory for athletes. To this end, this questionnaire was translated into Persian in several stages and sent to 7 sports psychologists to examine its content validity based on the criteria of content validity index and ratio. These experts approved the content validity of the Persian version. Subsequently, the questionnaire was distributed among 425 athletes with different skill levels in both team and individual sports. The data were analyzed using confirmatory factor analysis. The results showed good fit of the data to the model (RMSEA=0.048, NFI=0.927, CFI=0.945, X2/df=1.67). The internal consistency of the subscales was examined using Cronbach's alpha formula. The alpha coefficients were found to be 0.763 and 0.814 for the subscales of approach style and avoidance style, respectively, which indicated good reliability of the scale. It can be concluded that Coping Style Inventory for athletes was an appropriate instrument to study sports stress and coping strategies in Iranian samples.